Greeks, Jews, heretics, and the Church of God - Akselberg, K (2017)
The following study seeks to explore the subjects of Christianisation and Christian identity during the transitional period of the fourth century from an ecclesiological perspective, and argues that the very question of Christian identity is, indeed, an ecclesiological one. It approaches the subject through the writings of Cyril of Jerusalem, specifically his Catechetical Lectures, the earliest complete catechetical programme that has come down to us, making it an invaluable resource for anyone hoping to understand the Catholic Church’s efforts to preserve and construct its identity in the wake of Constantine’s formal conversion to its faith. Moreover, Cyril, who became bishop of the Holy City around 350, affords us a unique perspective on the question at hand, teaching as he did from the “very centre of the earth”, following the creation of a Christian holy land and pilgrimage centre in the midst of what remained a largely pagan province, and in a city still central to Judaism. The ability to possess the sites and relics associated with the life of Christ and the Prophets for the first time in Christian history not only made the drama of salvation tangible in Jerusalem like nowhere else, but raised new and important questions around the extent to which this sacred topography was compatible with Christianity's departure from the temple-centred worship of the Old Testament. It also provides valuable insight into the relationship between the local and the universal as regards notions of the Church’s catholicity, Cyril's definition of καθολική in his eighteenth lecture arguably being the earliest. Membership of the Church, and therefore Christian identity, is for Cyril primarily ontological, defined and effected through mysteriological participation, with baptism — the believer's death, rebirth, and union with Christ — representing the dividing line between insider and outsider, a fact enforced by the so-called Disciplina Arcani, by which all knowledge of the Church's sacraments were jealously guarded from the unbaptised. The thesis explores how this notion of ontological membership underpins and informs Cyril's dealings with the various groups against which he sought to define his own community — the Greeks, Jews, and heretics — while also looking at the ecclesiological significance of the baptismal act itself.